Anxiety and neurometabolite levels in the hippocampus and amygdala after prolonged exposure to predator-scent stress - O. B. Shevelev; V. E. Tseilikman; N. V. Khotskin; А. S. Khotskina; G. V. Kontsevaya; M. S. Lapshin; M. P. Moshkin; M. V. Komelkova; I. V. Feklicheva; O. B. Tseilikman; E. B. Manukhina; H. F Downey; et al. (Вавиловский журнал генетики и селекции)
Here, to study the relationship between anxiety levels with changes in the neurometabolic profile in the hippocampus and amygdala, an experimental predator stress model was reproduced in which Sprague-Dawley rats were exposed to cat urine for 10 minutes on a daily basis for 10 days. At the time of presentation of the stimulus, an online survey of behavioral reactions was conducted. Fear, aggressiveness, avoidance of stimulus and grooming were recorded. Fourteen days after the completion of the last stress exposure, the total level of anxiety was determined in the test of the“cross maze”. Using the method of in vivo NMR spectroscopy, the content of neurometabolites was determined in the hippocampus and in the amygdala. According to the peculiarities of behavioral reactions to a stressor, animals were retrospectively divided into two phenotypes. The first phenotype used a passive behavioral strategy, and the second phenotype was active. In animals of the first phenotype, the indicators of anxiety behavior remained at the control level. In animals of the second phenotype, a decrease in anxiety was observed. Animals of the second phenotype showed elevated levels of lactate in the hippocampus compared to animals of the first phenotype, and the lowest N-acetylaspartate levels significantly differed from those in the control and the first phenotype animals. In the amygdala, in animals of the second phenotype, the content of taurine is sharply reduced in comparison with those in the control and the animals of the first phenotype. Thus, the results obtained indicate a relationship of post-stress changes in anxiety, with the peculiarities of the behavioral reactions presented at the moment of the immediate action of the stressor. Among the hippocampal and amygdala neurometabolites, the most informative for the characterization of the anxiolytic action of the predator stress are identified.